(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Tendency of what on today’s a day general educational," "question of технологияландыру in science of pedagogics spacious and examined in detail. That technologies educating row in process wrapping up nowaday educating large pedagogical taken away. Settling such a scientific approach, perfected professional qualification teacher, on to teach to arrive at in lower result technologies, that guarantee, first is technology problem educating. From it approach on giving, problem education on places of that pedagogical supreme educational in the article, that was named, author, tried to examine features of features. Because only what searches activist interest of cognizableness readers of technology problem educating needs, that to increase. Intellectual an aim putting in time and give an opportunity to bear and reading real look, said that to apply elements problem educating in process Educating to life, working, to decide teaches vital problems. That elements problem educating wrapping up an author on teaches as advantageous to the use болатындығын discusses. . In the article the features of problem-based learning in the pedagogical university. The author refers to the principles of the learning process, to provide a method of problem situations in the classroom, and argues for the benefits of problem-based learning. The relevance of this article is not in doubt, since the elements of problem teaching motivate students to independently search for information, and stimulate thinking and, therefore, do not abstract knowledge, and personal and meaningful. They allow you to teach yourself to see the problem, formulate it, to find solutions and solve it.